PENGARUH KEPEMILIKAN ASURANSI KESEHATAN PADA KELOMPOK MISKIN TERHADAP UTILISASI PELAYANAN KESEHATAN DI INDONESIA: SEBUAH STUDI RETROSPEKTIF - Wanti, Dian Ira (UI Scholars Hub, 2023)
Health is the main priority of the Indonesian government in order to improve the health status of the Indonesian people in order to become a healthy, qualified and productive society. Health insurance is one of the programs held by the government to make this happen. Health insurance ownership from year to year continues to increase, but this increase is not accompanied by high utilization of health services, both outpatient and inpatient. The low utilization of health services raises the questions of how health insurance ownership affects the utilization of health service utilization. Therefore, this study aims to analyze the impact of health insurance on health service utilization in Indonesia. This study uses the Propensity Score Matching method. The sample used was IFLS 5 2014 data in the form of individuals who received Social Protection Cards (KPS), totaling 22,500 individuals. The dependent variable were frequency of outpatient use in the last 4 weeks and frequency of inpatient use in the last 12 months. This study found that the health insurance variable had a negative effect on inpatient utilization with a significance level of 10%. However, it has a positive effect on outpatient utilization at the 5% significance level. The results showed that having health insurance can increase outpatient utilization by 14.6% higher than individuals who do not have health insurance.